Theoretical Interpretation of Business Processes in Insurance Activity: Generality and Specificity - Yakubova N. T. (Research Parks Publishers, 2022)
The components of business processes include the creation of new products, sales, services, forecasting, human resource management and other activities aimed at improving operational efficiency.